Power Spectral Density Error Analysis of Spectral Subtraction Type of Speech Enhancement Methods. (18th September 2006) - Händel Händel, Peter Peter
Abstract : A theoretical framework for analysis of speech enhancement algorithms is introduced for performance assessment of spectral subtraction type of methods. The quality of the enhanced speech is related to physical quantities of the speech and noise (such as stationarity time and spectral flatness), as well as to design variables of the noise suppressor. The derived theoretical results are compared with the outcome of subjective listening tests as well as successful design strategies, performed by independent research groups.